# 2p^2+2p-12=-2p^2

## Simple and best practice solution for 2p^2+2p-12=-2p^2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 2p^2+2p-12=-2p^2 equation:

2p^2+2p-12=-2p^2
We move all terms to the left:
2p^2+2p-12-(-2p^2)=0
We get rid of parentheses
2p^2+2p^2+2p-12=0
We add all the numbers together, and all the variables
4p^2+2p-12=0
a = 4; b = 2; c = -12;Δ = b2-4acΔ = 22-4·4·(-12)Δ = 196The delta value is higher than zero, so the equation has two solutionsWe use following formulas to calculate our solutions:$p_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$p_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{196}=14$
$p_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(2)-14}{2*4}=\frac{-16}{8} =-2$
$p_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(2)+14}{2*4}=\frac{12}{8} =1+1/2$

`